2012
DOI: 10.1111/j.1469-8137.2012.04302.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and evolutionary costs of herbivory defense: systems biology of glucosinolate synthesis

Abstract: SummaryHere, we describe our updated mathematical model of Arabidopsis thaliana Columbia metabolism, which adds the glucosinolates, an important group of secondary metabolites, to the reactions of primary metabolism. In so doing, we also describe the evolutionary origins of the enzymes involved in glucosinolate synthesis. We use this model to address a long-standing question in plant evolutionary biology: whether or not apparently defensive compounds such as glucosinolates are metabolically costly to produce.W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
126
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 166 publications
(132 citation statements)
references
References 81 publications
(126 reference statements)
3
126
0
3
Order By: Relevance
“…spines and trichomes) and specific chemical compounds. Constitutive defense mechanisms provide immediate protection against herbivore attacks, although they represent an energy investment by the plant regardless of whether herbivory occurs or not (Mauricio, 1998;Bekaert et al, 2012). By contrast, inducible defense mechanisms do not require an up-front energy cost, although such mechanisms may not be as immediate as constitutive ones when herbivore feeding occurs (Windram et al, 2012).…”
mentioning
confidence: 99%
“…spines and trichomes) and specific chemical compounds. Constitutive defense mechanisms provide immediate protection against herbivore attacks, although they represent an energy investment by the plant regardless of whether herbivory occurs or not (Mauricio, 1998;Bekaert et al, 2012). By contrast, inducible defense mechanisms do not require an up-front energy cost, although such mechanisms may not be as immediate as constitutive ones when herbivore feeding occurs (Windram et al, 2012).…”
mentioning
confidence: 99%
“…Combined with the guiltby-association principle (Bino et al, 2004;Saito et al, 2008), omics analyses allow the prediction of unknown gene and metabolite functions. For instance, the systematic metabolomics approach has helped to determine the biosynthetic regulation of glucosinolates by MYB transcription factors (Hirai et al, 2007;Sønderby et al, 2007) and to model the costs of glucosinolate biosynthesis in terms of primary metabolism (Bekaert et al, 2012). This data-driven (top-down) strategy can guide the development of new hypotheses about regulatory and metabolic pathways, which may subsequently predict the emergence of certain phenotypes (Fukushima et al, 2009;Saito and Matsuda, 2010).…”
mentioning
confidence: 99%
“…Allocation of glucosinolates could be one of the tolerance strategies to cope with stressful conditions with relative low energy cost. A direct allocation of glucosinolates production in Arabidopsis with an increase in photosynthetic energy has been reported by Bekaert et al [109]. These all findings indicated that salt-induced increases in glucosinolates content may be involved in the salt stress response of plants but the effects of salinity on glucosinolates biosynthesis and metabolism need further attention at molecular and cellular levels.…”
Section: Glucosinolatesmentioning
confidence: 77%